Flexicurity in Belgium: A Proposal Based on Economic Principles - Bart Cockx; Bruno Van der Linden (Institute for the Study of Labor (IZA), 2009)
The current unemployment insurance and employment protection legislation were set up in an economic environment in which relationships between workers and firms were typically long-lasting and stable. The increasing globalisation of the economy and the rapid technological and organisational changes require more flexibility of both workers and firms leading to career paths which are much more volatile both within and between firms. Current institutions must be therefore urgently reformed to reconcile this new need of more flexibility with that of security for workers. The call for flexicurity is not new, but there is no unanimity on the corresponding institutional model it implies. Rather than proposing a reform on the basis of existing institutions abroad, we propose a reform that is explicitly guided by economic principles. In a nutshell, we propose to transform the bulk of the advance notice payments by a unique lay-off contribution, independently of the type of worker (blue or white-collar) and type of contract (temporary or open-ended). A severance payment, less important than the lay-off contribution, is due to cover the psychic cost related to dismissal. In order to make the employer accountable for the costs he imposes on society, the lay-off contribution should be made proportional to the cumulative past earnings since the moment that the worker was hired in the firm. This contribution would be used not only to finance a supplement to the current unemployment benefits, but also, as to make the worker more accountable, to finance active labour market policies for the unemployed. Aside of this scheme, it makes sense to generalise the current scheme of temporary unemployment benefits for blue-collar workers to white-collar workers, but only to the extent that one introduces experience rating in the funding, so that again the employers are made accountable for the social costs that they induce by these temporary lay-offs.
Keywords: H11; H21; H23; J65; J68; 330; lexicurity; employment protection; unemployment insurance; active labour market policies; optimal design; Flexicurity; Arbeitsmarktflexibilität; Soziale Sicherheit; Sozialreform; Arbeitslosenversicherung; Kündigungsschutz; Arbeitsbeziehungen; Belgien